The Regulatory Role of Oxygen Metabolism in Exercise-Induced Cardiomyocyte Regeneration - Bo, Bing; Li, Shuangshuang; Zhou, Ke; Wei, Jianshe (Frontiers in Cell and Developmental Biology, 2021)
During heart failure, the heart is unable to regenerate lost or damaged cardiomyocytes and is therefore unable to generate adequate cardiac output. Previous research has demonstrated that cardiac regeneration can be promoted by a hypoxia-related oxygen metabolic mechanism. Numerous studies have indicated that exercise plays a regulatory role in the activation of regeneration capacity in both healthy and injured adult cardiomyocytes. However, the role of oxygen metabolism in regulating exercise-induced cardiomyocyte regeneration is unclear. This review focuses on the alteration of the oxygen environment and metabolism in the myocardium induced by exercise, including the effects of mild hypoxia, changes in energy metabolism, enhanced elimination of reactive oxygen species, augmentation of antioxidative capacity, and regulation of the oxygen-related metabolic and molecular pathway in the heart. Deciphering the regulatory role of oxygen metabolism and related factors during and after exercise in cardiomyocyte regeneration will provide biological insight into endogenous cardiac repair mechanisms. Furthermore, this work provides strong evidence for exercise as a cost-effective intervention to improve cardiomyocyte regeneration and restore cardiac function in this patient population.